Assessing the quality of decision-making of expert rugby players - Claasen, P. J. (University of Pretoria, 2008)
The study of cognition as it relates to expert performance in sport is an area that has received increased attention over the last 25 years. This has been made possible by the fact that the domain of sport offers a rich and diverse setting in which to study cognition and its links to human performance, coupled with the abundant supply of highly practiced athletes providing unique opportunities to study these factors in a natural environment. The quality of on-field decision-making of expert athletes has received attention in a number of open-skill sporting codes, including basketball, field hockey and soccer. Decision-making quality of expert athletes in rugby union, as an invasive, open-skill sporting code, has not received the same amount of attention.